Rancang Bangun Sistem Transaksi Service Laptop Dan Komputer Berbasis Web Di CV . Jayla Tech ID - Ridho Pijak Imana; Alfin Hidayat; Farizqi Panduardi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
CV. Jayla Tech .ID is a laptop and computer services company that still uses manual transactions and reports to manage its business. This causes problems that arise, including frequent loss of transaction note data or damage to transaction notes, resulting in history data when warranty claims have no evidence of damage and transactions. So an application was created to design a web-based laptop and computer service transaction system which aims to make transactions and warranty claims easier, assisting the Admin in reporting a recap of the overall profit and loss results at CV. Jayla Tech .ID. Data collection was carried out through interviews, literature study and observation. The Rapid Application Development (RAD) method is used in developing service transaction systems, including requirements planning, system design, planning and implementation. The planning stage requires several actors such as admin and cashier. System design using Use Case and Entity Relationship Diagram (ERD). At the design stage, coding is carried out according to the system design required by the company and according to the agreement. The testing method carried out in this research is the User Acceptance Test (UAT). User Acceptance Test testing is a test that involves users directly using the system that has been built. This test uses (UAT) type of Contract Acceptance Testing (CAT), namely testing that is based on the requirements and criteria that have been agreed in the contract. The results of this research match the user's desired features and are very helpful for managing service and sales transactions on CV. JAYLA TECH .ID.